Ecological studies of mayflies (Insecta, Ephemeroptera): can sampling effort be reduced without losing essential taxonomic and ecological information? - SHIMANO, Yulie (Instituto Nacional de Pesquisas da Amazônia, 2019)
The present study evaluated the potential for the reduction of sampling effort in studies of ephemeropteran nymphs in Brazilian Amazon streams, Pará State, Brazil, without the loss of ecological information (species composition, abundance, and richness), and the congruence of different levels of taxonomic resolution (morphospecies, genus, family and functional group). Test groups of 15, 10 and five subsamples were selected from the 20 subsamples collected per stream (40 streams sampled), and were compared in terms of their species richness and abundance (ANOVA), and composition (Procrustes). Taxonomic resolution was also analyzed in Procrustes. Species abundance (F(3, 156) = 25.426; p < 0.001) and richness (F(3, 156) = 13.866, p < 0.001) varied significantly among sample groups, while the results of the 15-S group were statistically similar, in both cases, to those of the 20-S group. A similar pattern was found for species composition. The genus-level taxonomic resolution produced results 99% similar to those found for the species-level data. The results indicate that the reduction in sampling effort from 20 to 15 subsamples per site and a genus-level taxonomic resolution would not affect the reliability of analyses significantly. A reduction of five samples per site would result in a decrease of effort in the field and the amount of material to be processed, reducing laboratory time. In addition to a reduction in the time and resources needed to identify specimens, the adoption of a genus-level taxonomic resolution could help minimize errors of under- or over-estimation in the processing of the results.